2022
DOI: 10.1093/nar/gkac747
|View full text |Cite
|
Sign up to set email alerts
|

EWS/FLI mediated reprogramming of 3D chromatin promotes an altered transcriptional state in Ewing sarcoma

Abstract: Ewing sarcoma is a prototypical fusion transcription factor-associated pediatric cancer that expresses EWS/FLI or a highly related FET/ETS chimera. EWS/FLI dysregulates transcription to induce and maintain sarcomagenesis, but the mechanisms utilized are not fully understood. We therefore sought to define the global effects of EWS/FLI on chromatin conformation and transcription in Ewing sarcoma cells using a well-validated ‘knock-down/rescue’ model of EWS/FLI function in combination with next generation sequenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 90 publications
4
17
0
Order By: Relevance
“…CUT&Tag experiments were carried out for 2 biological replicates of CTCF and H3K27ac and 3 biological replicates for FLAG tagged DBD and DBD+ constructs. An in-house pipeline was used to analyze CUT&Tag data (Boone et al, 2021;Showpnil et al, 2022). Quality control on raw sequencing reads were performed with FastQC (v0.11.4) (Andrews, 2010).…”
Section: Cutandtag Data Processing and Analysismentioning
confidence: 99%
“…CUT&Tag experiments were carried out for 2 biological replicates of CTCF and H3K27ac and 3 biological replicates for FLAG tagged DBD and DBD+ constructs. An in-house pipeline was used to analyze CUT&Tag data (Boone et al, 2021;Showpnil et al, 2022). Quality control on raw sequencing reads were performed with FastQC (v0.11.4) (Andrews, 2010).…”
Section: Cutandtag Data Processing and Analysismentioning
confidence: 99%
“…Phase separation such as liquid-liquid phase separation (LLPS) was proposed to be crucial for transcriptional control and chromatin structure organization ( Hnisz et al, 2017 ). Ahn et al (2021) have demonstrated that NUP98-HOXA9, an oncogenic transcription factor (TF) with potent LLPS capability, mediates CTCF-independent DNA loops among cognate NUP98-HOXA9-bound sites, forming long-range E:P contacts, and that such a looping mechanism requires the presence of NUP98-HOXA9’s intrinsically disordered regions (IDRs), which is essential for LLPS; similar looping was also reported for another cancer-related TF, EWS-FLI ( Showpnil et al, 2022 ). Moreover, a recent work indicated that LLPS plays a role in weakening the insulation properties of a subset (∼20%) of TAD boundaries, which exhibit the feature of “house-keeping” genes, high transcription and a lack of CTCF ( Gamliel et al, 2022 ).…”
Section: Polycomb Repressive Complex-mediated and Ccctc-binding Facto...mentioning
confidence: 69%
“…the BAF complex) and induction of an oncogenic gene-expression program [ 124 ]; also, fusing a minimal LLPS-inducing IDR sequence to FLI was sufficient to recapitulate the EWS-FLI-related activities [ 124 ]. A more recent study further reported that EWS-FLI induces looping [ 125 ], reminiscent of what was observed with NUP98-HOXA9 [ 82 ]. Specifically, new DNA loops are formed with their anchors associated with binding of EWS/FLI and not CTCF [ 125 ]; in addition, EWS/FLI binds to the GGAA-rich motifs in the genome of Ewing’s sarcoma, leading to new enhancer formation, A-type compartmentalization, and target gene upregulation [ 125 ].…”
Section: Idp-/idr-dependent and Phase Separation-driven Chromatin Loo...mentioning
confidence: 73%